1985
DOI: 10.1055/s-2007-1014086
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic Pseudoaneurysm after Aorto-coronary Bypass Grafting

Abstract: A patient with a pseudoaneurysm at the site of the distal anastomosis of a saphenous vein coronary bypass graft is described. The aneurysm was resected. To our knowledge this is the first report of this complication after coronary bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Anastomotic pseudoaneurysm after a CABG procedure has been reported in less than 1% of cases 10 11. These rare events occur mostly in degenerating grafts years after the bypass procedure.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…5.46 ). Aneurysms have also developed at the site of coronary anastomosis of vein bypass grafts [ 531 ]. Pseudoaneurysms can occur after coronary rupture from balloon dilation (Fig.…”
Section: Coronary Artery Aneurysmsmentioning
confidence: 99%